OPTIMUM SATELLITE LAUNCHER TRAJECTORY GUIDED WITH PROPORTIONAL NAVIGATION PLUS GRAVITY COMPENSATION GUIDANCE (Journal of Engineering, 2006)
The optimum trajectory of a single or multi-stage satellite launcher guided with proportionalnavigation guidance (PNG) is addressed. The PNG is extended to compensate for the gravity effect.For the trajectory optimization problem, the launcher is modeled as a mass point flying around thecenter of the Earth. To provide a completely valid analysis, all known influences on the launchertrajectory have been considered; Empirical equations have been used in order to model the Earthstandard atmosphere in SI units. A computer program had been constructed in order to simulate thetrajectory of such launcher from the available initial conditions. Pegasus launcher is used as ahypothetical example. The simulator results show that the proportional navigation plus gravitycompensation guidance gives fairly accurate results.